Legal Standing of Customary Land in Indonesia: A Comparative Study of Land Administration Systems - Mustafa Bola (Faculty of Law, Hasanuddin University, 2017)
Prove of land ownership by customary land is generally unwritten, just a confession of the surrounding communities with nature sign boundaries. If land ownership cannot be supported by strong evidence, the land may be registered by someone else who has getting physically for 20 years or more in consecutively and qualified on Government Regulation No. 24 of 1997 concerning Land Registration. Proof of old rights derived from the customary land law is rationally difficult to prove because there are no written documents. Customary land law does not know written ownership, only physical possession continually so it is very prone to conflict or dispute. In order to develop land administration in Indonesia, the values of customary land law contained in its principles is expected to be reflected in the land administration so it can reduce land conflict in the community. The role of customary land law has a large portion of the national land law. The role of government or ruling is very important to create a conducive condition in the land sector. A land is not allowed for personal or group interests, its use must be adjusted with the condition and the characteristic of their rights so useful, both for the prosperity and helpful to community and state.